Pengaruh Penerimaan Pajak dan Dana Alokasi Umum (DAU) Terhadap Kemampuan Belanja Pemerintah Sebelum Covid-19 - Hermi Oppier; Hendri D Hahury; Izaac T Matitaputty; Amin Ramly (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research aims to determine the effect of tax revenue and the General Allocation Fund on the spending ability of the Ambon City government prior to the COVID-19 pandemic, using a 10-year period data from the Regional Government Budget of Ambon City obtained from the Ministry of Finance of the Republic of Indonesia, Directorate General of Fiscal Balance available online. The data collected was in the form of annual reports, with a total of 10 annual financial reports of Ambon City. The data was analyzed using classical assumption analysis and multiple linear regression analysis. The results show that both partially and simultaneously, the Regional Tax and General Allocation Fund have a significant effect on the capital expenditure of the Ambon City government. In other words, the higher the Regional Tax and General Allocation Fund, the higher the capital expenditure of the Ambon City government. This condition indicated that the Ambon City was still heavily reliant on the central government transfers. In fact, the Ambon City government should be able to optimize the sources of Local Own-Source Revenue and develop the region’s potential, such as the tourism sector, so that it could be independent in financing the regional economic development. This finding is also supported by the results of testing the coefficient of determination, where the R-square value is 0.951096 (95.1%), suggesting that the Regional Tax and General Allocation Fund could explain 95.1% of the capital expenditure of the Ambon City government, while the remaining 4.9% could be explained by other variables not included in the study.